Dynamizace vstupní kontroly za pomocí statistické přijímky srovnáváním - Majerek, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Diplomová práce se v teoretické části zabývá popisem metod výběrové kontroly s důrazem na statistickou přejímku srovnáváním. V praktické části je analyzován systém vstupní kontroly v závodu Siemens elektromotory Frenštát. Výstupem práce je směrnice o vstupní kontrole vytvořená v souladu s požadavky vedení organizace a vycházející z norem ČSN ISO 2859.

This master´s thesis deals with the description of control selection methods with emphasis on sampling procedures for inspection by attributes in the theoretical part. In the practicel part, the input control system in the plant Siemens motors Frenstat is analyzed. The outcome of the thesis is the direction of the input control created in accordance with the requirements of the management of the organization and based on ISO 2859 standards.
Dynamization of input control by sampling procedures for inspection by attributes
Keywords: Vstupní kontrola; statistická přejímka srovnáváním; Input control; sampling procedures for inspection by attributes